2019
DOI: 10.1002/humu.23870
|View full text |Cite|
|
Sign up to set email alerts
|

Biallelic variants in CTU2 cause DREAM‐PL syndrome and impair thiolation of tRNA wobble U34

Abstract: The wobble position in the anticodon loop of transfer ribonucleic acid (tRNA) is subject to numerous posttranscriptional modifications. In particular, thiolation of the wobble uridine has been shown to play an important role in codon‐anticodon interactions. This modification is catalyzed by a highly conserved CTU1/CTU2 complex, disruption of which has been shown to cause abnormal phenotypes in yeast, worms, and plants. We have previously suggested that a single founder splicing variant in human CTU2 causes a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…A number of evidences showed that tRNA 2-thiolation in U 34 has important roles in decoding and translation, and its defectiveness leads to various diseases in humans and pleotropic phenotypes in yeast 21,25,26 . In yeast, lack of the U 34 thiolation results in protein misfolding and aggregation 27 , inability to maintain metabolic homeostasis 15,28 , defects in invasive growth 29 , and hypersensitivity to various abiotic stresses 30,31 .…”
mentioning
confidence: 99%
“…A number of evidences showed that tRNA 2-thiolation in U 34 has important roles in decoding and translation, and its defectiveness leads to various diseases in humans and pleotropic phenotypes in yeast 21,25,26 . In yeast, lack of the U 34 thiolation results in protein misfolding and aggregation 27 , inability to maintain metabolic homeostasis 15,28 , defects in invasive growth 29 , and hypersensitivity to various abiotic stresses 30,31 .…”
mentioning
confidence: 99%
“…Notably, defects in tRNA modification have emerged as the cause of diverse neurological and neurodevelopmental disorders, thereby highlighting the critical role of tRNA modification in human health and physiology (Angelova et al, 2018; Ramos & Fu, 2019). In particular, the brain appears to be sensitive to any perturbation in translation efficiency and fidelity brought about by defects in tRNA modifications, as evidenced from the numerous cognitive disorders linked to tRNA modification enzymes such as: the Elongator complex (Hawer et al, 2018; Kojic & Wainwright, 2016); ADAT3 (Alazami et al, 2013; El‐Hattab et al, 2016; Ramos, Han, et al, 2019); NSUN2 (Abbasi‐Moheb et al, 2012; Khan et al, 2012; Martinez et al, 2012); FTSJ1 (Dai et al, 2008; Freude et al, 2004; Froyen et al, 2007; Gong et al, 2008; Guy et al, 2015; Ramser et al, 2004; Takano et al, 2008); WDR4 (Chen et al, 2018; Shaheen et al, 2015; Trimouille et al, 2018); KEOPS complex (Braun et al, 2017); PUS3 (Abdelrahman, Al‐Shamsi, Ali, & Al‐Gazali, 2018; Shaheen, Han, et al, 2016); CTU2 (Shaheen, Al‐Salam, El‐Hattab, & Alkuraya, 2016; Shaheen, Mark, et al, 2019); TRMT10A (Gillis et al, 2014; Igoillo‐Esteve et al, 2013; Narayanan et al, 2015; Yew, McCreight, Colclough, Ellard, & Pearson, 2016; Zung et al, 2015); PUS7 (de Brouwer et al, 2018; Shaheen, Tasak, et al, 2019); and ALKBH8 (Monies, Vagbo, Al‐Owain, Alhomaidi, & Alkuraya, 2019).…”
mentioning
confidence: 99%
“…In the yeast Saccharomyces cerevisiae, lack of cytoplasmic tRNA modifications causes varied phenotypes including slow growth, temperature sensitivity, and lethality (Hopper, 2013). Likewise, defects in cytoplasmic tRNA modifications cause human neurological disorders including familial dysautonomia (5)(6)(7) and numerous types of intellectual disability (ID), often with accompanying disease phenotypes (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Moreover, genes encoding tRNA modification enzymes or predicted modification enzymes have been linked to other diseases, including many mitochondrial disorders (25,26) and cancer (27).…”
Section: Introductionmentioning
confidence: 99%